National level data analysis of facial lacerations in Korea using the National Health Insurance Service (NHIS) database - Mo, Young Woong (Medicine (Baltimore), 2021)
No national epidemiological investigations have been conducted recently regarding facial lacerations. The study was performed using the data of 3,634,229 people during the 5-year period from 2014 to 2018 archived by the National Health Information Database (NHID) of the Health Insurance Review and Assessment Service. Preschool and children under 10 years old accounted for about one-third of patients. Facial lacerations were concentrated in the “T-shaped” area, which comprised forehead, nose, lips, and the perioral area. The male to female ratio for all study subjects was 2.16:1. Age and gender are significantly related with each other (P < .001). Mean hospital stays decreased, and numbers of outpatient department visits per patient were highest for hospitals and lowest for health agencies. Over the study period, hospital costs per patient in tertiary and general hospitals increased gradually. Preschool and school-aged children are vulnerable to trauma. Male patients outnumbered female patients by a factor of more than 2. The “T-shaped’” area around forehead is vulnerable to injury. Total cost of medical care benefits per patient in tertiary hospitals was about 7 times on average than in health agencies. Regarding functional, behavioral, and aesthetic outcomes, more attention should be paid to epidemiologic data and hospital costs for facial lacerations.